ONLINE LEARNING STRATEGY DURING COVID-19 PANDEMIC TO GROW SCIENCE’S LEARNING INTEREST - Ilmi Firdaus; Erman Erman (Jurusan IPA, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Negeri Surabaya, 2022)
This research aims to find out and explore information related to the application of online learning strategies used by science teachers during the learning process in Covid-19 pandemic to foster student’s interest in learning science. This research method uses the case study method. The subjects in this study were 8 science teachers and 26 students from SMP Negeri 2 Mojokerto City and SMP Negeri 4 Mojokerto City. The selection of this school is based on the ranking of the best public junior high schools in Mojokerto City which refers to the results of the 2019 National Examination, namely SMPN 2 Mojokerto has an average of 70.40 with 284 participants and SMPN 4 Mojokerto has an average of 65.01 with 239 participants. Instruments in this research is a teacher and student questionnaire which is presented in the form of Google Forms and hard files. Data collection techniques in this study were unstructured interviews, observation, and documentation. The data analysis technique in this study is descriptive analysis by determining the percentage of respondents' answers. The results in this study are 63% of science teachers have implemented online learning strategies during the Covid-19 pandemic. The synchronous discussion method is a learning method that is often applied by science teachers when learning online. The conclusion of this research is that the students' interest and attention to the learning strategies and methods applied by the teacher are able to foster students' interest in learning science.